THE STUDY OF FOLKLORE, edited by Alan Dundcs: Prentice-Hall, Ind., Englewood Cliffs, New Jersey. 482 pp. with 35 illustrations and drawings, six musical illust. and 15 comprehensive maps - Basil, Brother (International Library of African Music, 1965)
pages: 84
Keywords: African Music